2021
DOI: 10.1021/jacs.1c02148
|View full text |Cite
|
Sign up to set email alerts
|

Bright and Stable Light-Emitting Diodes Based on Perovskite Quantum Dots in Perovskite Matrix

Abstract: Light-emitting diodes (LEDs) based on metal halide perovskite quantum dots (QDs) have achieved impressive external quantum efficiencies; however, the lack of surface protection of QDs, combined with efficiency droop, decreases device operating lifetime at brightnesses of interest. The epitaxial incorporation of QDs within a semiconducting shell provides surface passivation and exciton confinement. Achieving this goal in the case of perovskite QDs remains an unsolved challenge in view of the materials’ chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
114
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(115 citation statements)
references
References 35 publications
1
114
0
Order By: Relevance
“…For example, to further increase the phase stability in Br/Cl mixed perovskite films, composition engineering will be a promising strategy to control halide migration and/or phase segregation to achieve highly efficient and stable PeLEDs. 36 , 55 , 56 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, to further increase the phase stability in Br/Cl mixed perovskite films, composition engineering will be a promising strategy to control halide migration and/or phase segregation to achieve highly efficient and stable PeLEDs. 36 , 55 , 56 …”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the efficiency and lifetime of our DPDA-perovskite-based PeLED devices still have room to further improve. For example, to further increase the phase stability in Br/Cl mixed perovskite films, composition engineering will be a promising strategy to control halide migration and/or phase segregation to achieve highly efficient and stable PeLEDs. ,, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the HRTEM images, the cubic NCs become truncated cubic NCs (Figure S1a-d ). Therefore, (110) crystal planes are more exposed and enhance the peak at 20° [ 47 , 48 ]. Furthermore, the morphology and size characterization for Ca 2+ -doped CsPbI 3 NCs were studied by TEM.…”
Section: Resultsmentioning
confidence: 99%
“…Yi-Xin also found that the CsPbBr 3 halide perovskite photocatalyst significantly affected the CO 2 reduction performance, achieving a higher reaction rate and long-term stability. Liu et al (2021) used strained perovskite QDs as nucleation centers to make the film crystallization more uniform and stable. This method reduced gradient crystallization and suppressed halide segregation, leading to the efficient transport of charge carriers, the red CsPbI 3 QDs films based LED showed external quantum efficiency (EQE) of 18% and remained half of the initial luminance even after 2,400 h working.…”
Section: Introductionmentioning
confidence: 99%